Increasing citizen and association involvement in government decision-making by implementing civic engagement platforms: Valencia city case study - Abdelfattah, Alaa Bakry Abdelaziz (2021)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies